Predicting Outcome in Organophosphorus Poisoning Using RBC Cholinesterase and Serum Cholinesterase Values: A Hospital-based Longitudinal Study - Kar, Saswati; Mohanty, Nihar Ranjan; Panda, Bhagyashree; Rattan, Roma; Choudhury, Anurag; Panda, Suchismita; Rout, Pramod Kumar; Das, Bhaktabandhu; Prusty, Biswaranjan; Thatoi, Pravat Kumar (Journal of Laboratory Physicians, 2023)
Background Organophosphorus (OP) poisoning is a leading cause of mortality due to self-harm in Asian countries, including India. Red blood cell cholinesterase (RBC-ChE) and serum cholinesterase (serum-ChE) levels are used for predicting outcomes. There is a paucity of literature studying the RBC-ChE levels in OP poisoning and comparing it with the serum-ChE levels.Methods This is a longitudinal study assessing the outcome in OP poisoning patients using the RBC-ChE and serum-ChE levels. Both enzyme levels are compared and correlated for adult patients presenting within 24 hours of consumption of the OP compound. Sensitivity and specificity are measured.Results Of the 99 OP poisoning patients included, 20 patients did not survive, and 23 patients required ventilatory support. At admission, RBC-ChE (median, interquartile range [IQR]) was significantly different between survivors (45.2 [30.5–60] U/g Hb) and nonsurvivors (6.3 [4.2–13.4] U/g Hb), while serum-ChE (median, IQR) was not statistically different (p = 0.061) between survivors (350 [247–670]) and nonsurvivors (290 [182–415.8]). Similarly, RBC-ChE was significantly different between patients requiring a ventilator and those not requiring a ventilator (6.8 vs. 44.2 U/g Hb), whereas the serum-ChE values measured on admission were not significantly different for patients requiring a ventilator versus those not requiring a ventilator (290 vs. 348 U/L; p = 0.119). At the cutoff of 20 U/g Hb, RBC-ChE had 90.5% sensitivity and 91% specificity in predicting mortality. Kaplan–Meier survival showed the probability of survival decreased to nearly 50% if the time to reach the hospital was ≥4 hours.Conclusion RBC-ChE was superior in predicting outcomes in OP poisoning patients compared with serum-ChE measured on the day of admission.
Keywords: cholinesterase; Kaplan–Meier; organophosphorus; pesticides; poisoning; RBC cholinesterase